Genetic resources of Spanish hulled wheats - Caballero L.; Martín L.M.; Alvarez J.B. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
Emmer (Triticum turgidum ssp. dicoccum Schrank em Thell, syn T. dicoccon Schrank) and spelt (T. aestivum ssp. spelta L. em Thell.) are two hulled wheats that are still grown in some Spanish regions, mainly in Asturias (North of Spain), where are indistinctly named as escanda. One recent collecting mission carried out in this Spanish zone has showed the scarce presence of emmer (4 populations), together with the presence of foreigner spelt that could change the genetic patrimony of the escanda, because of present agronomic characteristics more adapted to the present requirements than the autochthon spelt lines. This supposes one clear danger to the maintaining of these hulled wheats, together with the lost of diversity associated to them. The endosperm storage proteins have showed to be good markers for measure of this diversity. The analysis of the autochthon populations collected showed wide variation for the storage proteins, also as for morphological traits. In conclusion, we think that the evaluation of these genetic resources could be useful for enlarging the background of the modern wheats. Likewise, for the obtaining of escanda lines with better agronomical, morphological and quality traits than the actual lines, with the advantage of to be materials adapted to the special conditions of the cultivated zone.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)